Higher levels of anti-phosphorylcholine autoantibodies in early rheumatoid arthritis indicate lower risk of incident cardiovascular events - Sofia Ajeganova; Maria L. E. Andersson; Johan Frostegård; Ingiäld Hafström (Arthritis Research & Therapy, 2021)
Abstract Background The increased risk of cardiovascular events (CVE) in rheumatoid arthritis (RA) is not fully explained by traditional risk factors. Immuno-inflammatory mechanisms and autoantibodies could be involved in the pathogenesis of atherosclerotic disease. It has been suggested that anti-phosphorylcholine antibodies (anti-PC) of the IgM subclass may have atheroprotective effects. Here, we aimed to investigate the association between levels of IgM anti-PC antibodies with CVE in patients with early RA. Methods The study population was derived from the BARFOT early RA cohort, recruited in 1994–1999. The outcome of incident CVE (AMI, angina pectoris, coronary intervention, ischemic stroke, TIA) was tracked through the Swedish Hospital Discharge and the National Cause of Death Registries. Sera collected at inclusion and the 2-year visit were analyzed with ELISA to determine levels of anti-PC IgM. The Kaplan-Meier estimates and Cox proportional hazards regression models were used to compare CV outcome in the groups categorized by baseline median level of IgM anti-PC. Results In all, 653 patients with early RA, 68% women, mean (SD) age 54.8 (14.7) years, DAS28 5.2 (1.3), 68% seropositive, and without prevalent CVD, were included. During the follow-up of mean 11.7 years, 141 incident CVE were recorded. Baseline IgM anti-PC above median was associated with a reduction in risk of incident CVE in patients aged below 55 years at inclusion, HR 0.360 (95% CI, 0.142–0.916); in males, HR 0.558 (0.325–0.958); in patients with BMI above 30 kg/m2, HR 0.235 (0.065–0.842); and in those who did not achieve DAS28 remission at 1 year, HR 0.592 (0.379–0.924). The pattern of associations was confirmed in the models with AUC IgM anti-PC over 2 years. Conclusion Protective effects of higher levels of innate IgM anti-PC autoantibodies on CVE were detected in younger patients with RA and those at high risk of CVE: males, presence of obesity, and non-remission at 1 year.